ADAPTED EVALUATION PROTOCOLS FOR TEENAGE ATHLETES COMPETING AT YOUTH OLYMPIC GAMES: SAFEGUARDING AND PROTECTING YOUNG CHAMPIONS. Issue 4 (1st February 2017) - Adami, Paolo Emilio; Squeo, Maria Rosaria; Quattrini, Filippo Maria; Paolo, Fernando Maria Di; Pisicchio, Cataldo; Ciardo, Roberto; Verdile, Luisa; Caselli, Stefano; Maestrini, Viviana; Spataro, Antonio; Pelliccia, Antonio
Abstract : Background: Currently no clear indication are present for the pre-participation evaluation of adolescent elite athletes. Objective: Our objective was to assess the efficacy of a tailored pre-participation evaluation protocol to assess health and eligibility of adolescent athletes, shortlisted for participation in the Youth Olympic Games. Design Setting and Patients: Between 2010 and 2014, 247 adolescent elite athletes (53% females), mean age 16.3±1.01 years, competing in 22 summer and 15 winter sport disciplines, were evaluated through a tailored pre-participation protocol, which included 10 different health specialists. Main Outcome Measurements: In 36 of the 247 athletes (14.5%), the pre-participation evaluation led to the final diagnosis of a pathological condition, including CV in 17 (6.8%), pulmonary in 11 (4.5%), endocrine in 5 (2.0%), infectious, neurological and psychiatric disorders in 1 each (0.4%). Among CV abnormalities, atrial septal defects were observed in 9 (3.6%), valvular diseases in 5 (2.0%), primary tachyarrhythmias in 2 (0.8%) and hypertension in 1 (0.4%). Pulmonary diseases consisted of allergic asthma, diagnosed in 11. Endocrine diseases included Hashimoto's Thyroiditis in 2, Hypothyroidism in 2 and Androgen Insensitivity Syndrome in the remaining subject. Hepatitis B, Epilepsy Syndrome and Panic Disorder represented the remaining diagnoses, each in one individual. Results: Based on current National and International Recommendations, none of the athletes was considered at high risk for acute events and all were eligible to compete at the Youth Olympic Games. All athletes with pathological conditions or abnormal findings were required to undergo a periodic follow up. Conclusions: The specific pre-participation evaluation protocol implemented proved to be effective in identifying a wide range of disorders, in a significant proportion (14.5%) of adolescent Olympic athletes. The presented protocol should be considered for early identification of a wide spectrum of diseases in this population of athletes, allowing prompt treatment and minimising health consequences.